Impact of Chronic Drought on Nutritional Status of the Community in Drought affected areas in India - Kodavalla, Venkaiah; Kokku, Suresh Babu; Nimmathota, Arlappa; Kodavanti, Mallikharjun Rao; Ch, Gal Reddy; Kumar, Sharad; Manchala, Ravindranath; Avula, Laxmaiah; GNV, Brahmam (Indian Journal of Community Health, 2015)
Background: Communities affected by chronic drought conditions face a wide variety of challenges including an adverse effect on their nutritional status. The Government of India, during the year 2002-03, declared nine States viz., Andhra Pradesh, Karnataka, Tamil Nadu, Madhya Pradesh, Maharashtra, Rajasthan, Gujarat, Chhattisgarh and Orissa as drought affected. Material and Methods: At the request of Department of Agriculture, Government of India, a rapid community based cross-sectional study was carried out adopting multistage random sampling procedure with the objective to assess the nutritional status of community in these nine chronic drought affected states in India. Results: In general, the intakes of all the nutrients were grossly deficit as against their RDAs. The nutrition intervention programmes initiated by the Government of India, in general, contributed to meet the daily requirement of staples like cereals & millets in most of the States. Conclusion: In drought-affected areas, where the level of famine impact is unknown, an early rapid assessment of the nutritional status and the health needs of the population are critical to estimate the degree of impact to plan timely and appropriate interventions.